Business Process Management Workshops BPM 2013 International Workshops, Beijing, China, August 26, 2013, Revised Papers - Lohmann, Niels; Song, Minseok; Wohed, Petia; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book constitutes the refereed proceedings of nine international workshops held in Beijing, China, in conjunction with the 11th International Conference on Business Process Management, BPM 2013, in August 2013. The nine workshops comprised Business Process Intelligence (BPI 2013), Business Process Management and Social Software (BPMS2 2013), Data- and Artifact-Centric BPM (DAB 2013), Decision Mining and Modeling for Business Processes (DeMiMoP 2013), Emerging Topics in Business Process Management (ETBPM 2013), Process-Aware Logistics Systems (PALS 2013), Process Model Collections: Management and Reuse (PMC-MR 2013), Security in Business Processes (SBP 2013), and Theory and Applications of Process Visualization (TAProViz 2013). The 38 revised full papers presented were carefully reviewed and selected from 74 submissions.
Discovering and Navigating a Collection of Process Models using Multiple Quality Dimensions -- Discovering Stochastic Petri Nets with Arbitrary Delay Distributions From Event Logs -- Discovering Unbounded Synchronization Conditions in Artifact-Centric Process Models -- Uncovering the Relationship between Event Log Characteristics and Process Discovery Techniques -- Process remaining time prediction using query catalogs -- Discovering Block-Structured Process Models From Event Logs Containing Infrequent Behaviour -- Business Process Intelligence Challenge 2013 -- Enabling Workflow Composition within a Social Network Environment -- Towards A Meta-Model for Goal-Based Social BPM -- An experiment on the capture of business processes from knowledge workers -- ISEAsy: a social business process management platform -- Towards a Reference Implementation for Data Centric Dynamic Systems -- Synthesizing Object-Centric Models from Business Process Models -- Activity-centric and Artifact-centric Process Model Round trip -- Automatic Generation of Business Process Models based on Attribute Relationship Diagrams -- Enriching Business Process Models with Decision Rules -- Validating and Enhancing Declarative Business Process Models Based on Allowed and Non-Occurring Past Behavior -- Constructing Decision Trees from Process Logs for Performer Recommendation -- An Exploratory Approach for Understanding Customer Behavior Processes Based on Clustering and Sequence Mining -- The Design of a Workflow Recommendation System for Workflow as a Service in the Cloud -- Business Process Assignment and Execution from Cloud to Mobile -- Monitoring of Business Processes with Complex Event Processing -- Bringing Semantics to Aspect-Oriented Business Process Management -- Towards the Enhancement of Business Process Monitoring for Complex Logistics Chains -- Investigating Service Behavior Variance in Port Logistics from a Process Perspective -- A Petri Net Approach for Green Supply Chain Network Modeling and Performance Analysis -- Towards a DSL-based approach for specifying and monitoring home care plans -- Urban Congestion: Arrangement of Aamriw intersection in Bejaia's city -- Supply Chain Uncertainty under ARIMA Demand Process -- Methods for Evaluating Process Model Search -- Decomposition and Hierarchization of EPCs: A Case Study -- Process Model Fragmentization, Clustering and Merging: An Empirical Study -- Towards Measuring Process Model Granularity via Natural Language Analysis -- Automatic Extraction of Process Categories from Process Model Collections -- The Process Model Matching Contest 2013 -- Keynote: Specification and Conflict Detection for GTRBAC in Multi-domain Environment -- Multi-dimensional Secure Service Orchestration -- Explication of Termination Semantics as a Security-Relevant Feature in Business Process Modeling Languages -- Supporting Domain Experts to Select and Configure Precise Compliance Rules -- A Framework for the Privacy Access Control Model -- Role-based Access Control for Securing Dynamically Created Documents -- Towards Enhancing Business Process Monitoring with Sonification -- A Navigation Metaphor to Support Mobile Workflow Systems -- Evaluating KIPN for Modeling KIP.
Keywords: Computer science; Production management; Information technology; Business -- Data processing; Application software; Computer Science; Computer Appl. in Administrative Data Processing; IT in Business; Information Systems Applications (incl. Internet).; Operations Management; Electronic books